2019
DOI: 10.1186/s13071-019-3565-x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance mechanisms with novel ‘kdr’ type gene mutations in the tropical bed bug Cimex hemipterus

Abstract: Background The tropical bed bug, Cimex hemipterus , is a serious indoor public health pest in tropical regions causing intense physical discomfort and mental distress to humans. At present, the application of insecticides is the major control strategy. The present study was designed to evaluate the development of resistance and resistance mechanisms in Cimex hemipterus from Kandy district, Sri Lanka. Methods The resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…In this study, a similar phenomenon, resistance to insecticides, was found in the eld strains of C. hemipterus to different pyrethroids (bifenthrin, cypermethrin, esfenvalerate, and etofenprox) from Thailand [41], DDT and deltamethrin residues from Malaysia [44], a mixture of deltamethrin and imidacloprid from Australia [51], and permethrin and deltamethrin from Sri Lanka [26]. These conditions were also represented in different populations of the common bed bug for pyrethroids from USA [23], permethrin and deltamethrin from Australia [52], allethrin from Sydney [43], imidacloprid and β-cy uthrin from Malaysia [53,54], several neonicotinoids (imidacloprid, acetamiprid, thiamethoxam, and dinotefuran) from USA [55], bifenthrin from Germany [56], a mixture of deltamethrin and imidacloprid from Australia [52], and bendiocarb from Paris [57].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this study, a similar phenomenon, resistance to insecticides, was found in the eld strains of C. hemipterus to different pyrethroids (bifenthrin, cypermethrin, esfenvalerate, and etofenprox) from Thailand [41], DDT and deltamethrin residues from Malaysia [44], a mixture of deltamethrin and imidacloprid from Australia [51], and permethrin and deltamethrin from Sri Lanka [26]. These conditions were also represented in different populations of the common bed bug for pyrethroids from USA [23], permethrin and deltamethrin from Australia [52], allethrin from Sydney [43], imidacloprid and β-cy uthrin from Malaysia [53,54], several neonicotinoids (imidacloprid, acetamiprid, thiamethoxam, and dinotefuran) from USA [55], bifenthrin from Germany [56], a mixture of deltamethrin and imidacloprid from Australia [52], and bendiocarb from Paris [57].…”
Section: Discussionsupporting
confidence: 75%
“…These conditions were also represented in different populations of the common bed bug for pyrethroids from USA [23], permethrin and deltamethrin from Australia [52], allethrin from Sydney [43], imidacloprid and β-cy uthrin from Malaysia [53,54], several neonicotinoids (imidacloprid, acetamiprid, thiamethoxam, and dinotefuran) from USA [55], bifenthrin from Germany [56], a mixture of deltamethrin and imidacloprid from Australia [52], and bendiocarb from Paris [57]. Based on the bioassay results and the ndings of previous studies [26,41,44,51], all the bed bug populations in the present study manifested resistance to permethrin. Thus, the reconsideration of control methodologies is of paramount importance in the studied areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations in the voltage-gated sodium channel (VGSC) gene reduce the target-site sensitivity for pyrethroids and DDT, causing “knockdown resistance” ( kdr ) [ 23 , 24 ]. Three point-mutations are reported from C. lectularius (V419L, L925I, and I936F) and currently nine from C. hemipterus (L899V, M918I, D953G, Y/L995H, V1010L, I1011F, L1014F, V1016E, and L1017F/S) [ 25 , 26 ]. These mutations act by substituting the amino acid sequence of the VGSC protein that prevents the insecticide acting on the nervous system [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The school has six hostel accommodations for the students which are always almost packed beyond capacity, a condition that favours bedbug infestation A total of two hundred and seventy (270) bedbugs were harvested. Collections were done between 8pm − 10pm daily from May to August 2019 following the methods previously described by Punchihewa et al (2019). The collected bedbugs were transferred to the Yabatech Environmental Biology Laboratory in well labelled containers and they were maintained in aerated clean plastic containers at a temperature of 25 ± 2 o C and relative humidity of 75 ± 10%.…”
Section: Introductionmentioning
confidence: 99%